Modular Nanotransporters Delivering Biologically Active Molecules to the Surface of Mitochondria - Yuri V. Khramtsov; Alexey V. Ulasov; Tatiana A. Slastnikova; Andrey A. Rosenkranz; Tatiana N. Lupanova; Georgii P. Georgiev; Alexander S. Sobolev (MDPI AG, 2023)
Treatment of various diseases, in particular cancer, usually requires the targeting of biologically active molecules at a selected subcellular compartment. We modified our previously developed modular nanotransporters (MNTs) for targeting mitochondria. The new MNTs are capable of binding to the protein predominantly localized on the outer mitochondrial membrane, Keap1. These MNTs possessing antiKeap1 monobody co-localize with mitochondria upon addition to the cells. They efficiently interact with Keap1 both in solution and within living cells. A conjugate of the MNT with a photosensitizer, chlorin e6, demonstrated significantly higher photocytotoxicity than chlorin e6 alone. We assume that MNTs of this kind can improve efficiency of therapeutic photosensitizers and radionuclides emitting short-range particles.